Pendidikan Islam Inspiratif - Suparlan, Suparlan (Pascasarjana Universitas Islam Negeri Sultan Aji Muhammad Idris Samarinda, 2015)
Philosophical orientation of inspirational Islamic education should be universal-based education and multidimensional perspective (Good, human, and nature). It should enable to create the qualified future leaders who can play a role as rahmatan lil’alamin. Its objective is to reconstruct the experiences of human civilization and to fulfill human duties in developing the humanity. The model of inspirational Islamic education is directed to the quality of the educational processes and the teaching and learning, so that it could produce the human resources who has good competency that are needed in the society. The implementation of inspirational Islamic education involves all parties in the process of education, such as: teachers, teaching staffs, students and others who contribute the teaching and learning comprehensively. The teaching and learning of inspirational Islamic education involves three aspects, they are: experiences, reflection, and action. The experiences can be achieved not only from ourselves, but it also gained from the interaction with other people. The experiences are used to understand better, to find the meaning of humanity, to color the society, to encourage motivation, faith and belief. The output of inspirational Islamic education is the human who have good characters, beautiful attitude, skills, and the ones who always motivate themselves to be meaningful for his/her environment.